Risk factors for developing respiratory complications after coronary artery bypass surgery - Alisa Krdzalic; Amar Skakić; Harun Avdagić; Fuad Pašić; Tarik Odobašić; Goran Krdžalić (Medicinski glasnik, 2025)
Aim: : This study aims to identify independent risk factors associated with postoperative respiratory complications (PRC) in patients undergoing coronary artery bypass surgery (CABG). Methods: : A retrospective cohort study was conducted on 98 patients (82 male, 16 female) who underwent CABG at the Cardiovascular Surgery Clinic, University Hospital Tuzla. The incidence of PRC and potential risk factors were analyzed. Univariate analysis was performed to assess associations, followed by multivariable logistic regression to adjust for confounding factors. Independent risk factors were identified, including diabetes mellitus, smoking, hypertension, gender, and preoperative oxygen saturation <94%. Results: : PRC were observed in 48 patients (48.97%). Preoperative factors significantly associated with PRC included diabetes mellitus, smoking, hypertension, and low preoperative oxygen saturation. Intraoperative and postoperative factors, such as prolonged surgery duration (>180 min), mechanical ventilation >120 min, and blood transfusion exceeding 500 ml/24 h, were also identified as risk factors. Multivariable logistic regression confirmed that prolonged surgery duration, extended respiratory support, and transfusions >500 ml/24 h were independent predictors of PRC. Conclusion: : This study highlights the importance of perioperative risk stratification in preventing PRC. Reducing prolonged mechanical ventilation and minimizing unnecessary transfusions may improve postoperative outcomes. Further studies with larger cohorts are needed to refine risk prediction models and optimize perioperative management strategies.
Keywords: anaesthesia; blood transfusions; cardiac surgery; preventing; pulmonary